VD_FINDINFO Arrêt / 2018 / 642 vom 5. November 2018 - VD Tribunal cantonal (2018)
COTISATION AVS/AI/APG, FRAIS DE SOMMATION, AMENDE, RECONSIDÉRATION, FRAIS DE POURSUITE | 106 al. 1 CP, 88 LAVS, 43 al. 3 LPGA, 53 al. 3 LPGA, 34a RAVS, 36 RAVS, 38 RAVS